CONTROLE GENÉTICO DA RESISTÊNCIA DE MILHO À ANTRACNOSE DO COLMO - Máximo, Débora da Silva (2013)
The objectives of this study were to determine the genetic control of resistance to anthracnose stalk rot of corn and estimate the gene action involved in the generations descended from crosses between inbred lines of tropical maize. The estimation of genetic parameters was used to determine the mode of inheritance of resistance in nine families derived from crosses between resistant and susceptible inbred lines to Colletotrichum graminicola. Each family consisted of six generations (P1, P2, F1, RC1 and RC2), which were evaluated for resistance in two experiments implanted in a randomized block design in a split plot design, with three replications. Inoculations were performed using a suspension of 5 x 105 conidia mL-1 applied into the stalk. The quantification of the disease was performed using the external and internal length of lesion (cm), and number of internodes discolored. The three forms of assessment were effective in discriminating individuals resistant and susceptible to the pathogen. Through the analysis of mean generations, it was observed that there is great genetic variability among inbred lines used, where the LR 04-2 was the most effective in all families/ generations in which participated, always conditioning the lower values of lesion. The results indicated a similar mode of inheritance among families, with a predominance of additive genetic effects explaining 81.92% on average. The heritability coefficients (broad and narrow sense) were of high magnitude, indicating facility in the process of artificial selection by breeding programs. Estimates of heterosis were high and negative in all families studied, revealing the ability of resistant inbred lines to transfer the character resistance for the next generations, reducing the length of the lesions. The results showed that the genetic control of corn to anthracnose stalk rot is governed by a few genes of large effect on phenotypic expression. The addictive nature of inheritance, associated with higher estimates of heritability and oligogenic genetic control, infer that the genetic gains with selection will be successful in breeding programs that develop maize populations resistant to anthracnose stalk rot.